The Circular Economy Business Model of Algoland - J. Rosenlund; C. Legrand (Iranica Journal of Energy and Environment, 2019)
In the Algoland project, microalgae are used to clean water and air from industry. This is built on a long standing collaboration between research, industry and society. In this way Algoland supports the transition to a circular economy by turning pollution into biomass and potential products. This paper evaluates the potential for microalgae as an ecosystem service in industries from a circular economy perspective. The business model canvas was used in a workshop with stakeholders and researchers to discuss the challenges and opportunities for an industrial platform. Results showed that the established canvas model needs to be complemented by circular models; in order to be able to include ecosystem services. In this paper a circular canvas model is developed to be used in similar approaches.